Implementasi Model Pembelajaran Berbasis Konstruktivisme untuk Meningkatkan Kemampuan Komunikasi Matematik dan Kemandirian Siswa - Gultom, Diana Astria (NUCLEUS, 2024)
Lack of communication skills and independent learning mathematics student learning that takes place due to not construct students' thinking. As for the efforts is to apply contextual learning model based on constructivism that aims to: (1) improve the communication skills of mathematics students (2) increase the independence of student learning (3) determine the activities of active students (4) determine the ability of teachers to manage learning (5) analyzes the responses of the students in completing test students' mathematical communication skills.This type of research is a classroom action research (PTK) held at SMK Immanuel Medan. Research subjects of class X Motorcycle Engineering (TSM) in the school year 2014/2015 a total of 32 people. The object of this research is learning that applying a contextual model to determine the increase in active activity, communication skills and self-reliance mathematics students. This study consisted of two cycles of the first cycle and the second cycle consists of 8 meetings. The results of this study can be seen from (1) an increase in students' mathematical communication skills .. It can be seen in the results of the acquisition in the first cycle there are 25 students or 78.1% hav0e a minimum value of 2.67 and the second cycle increased to 31 students or 97%, and (2) an increase in student independence. This can be seen in the results of the acquisition in the first cycle there is a 33.13% has the lowest value and the second cycle increased by 89.84% (3) active activity of students in the first cycle there are five criteria observations have value - average 3.42 , the second cycle there are five criteria observations have value - average 4.81. (4) The process of settlement of the answers the students complete the ability and math students better communication.